2016
DOI: 10.1108/ijhrh-07-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Male perspectives on FGM among communities of African heritage in Italy

Abstract: Purpose – The purpose of this paper is to investigate the attitudes, knowledge and beliefs regarding female genital mutilation/cutting (FGM/C) of six groups of immigrant men from countries where FGM/C is practiced and to identify their role in the decision-making process of circumcising their daughters. Design/methodology/approach – The study took the form of qualitative action research with seven focus groups of 50 men coming from Somal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…15 Whilst not explicitly depicted on any of the campaign material posters or leaflets, the participants reported concern that FGM was seen as a practice related to Islam. Recent research has shown consistent confusion regarding whether FGM is dictated by Islam or not 7 and more work is needed to clarify this misperception. 3 Considering FGM is not a practice related to Islam, it is worth noting that religious leaders are often seen as 'guardians of the community' with the potential to reinforce campaign messages, an important aspect of creating successful campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Whilst not explicitly depicted on any of the campaign material posters or leaflets, the participants reported concern that FGM was seen as a practice related to Islam. Recent research has shown consistent confusion regarding whether FGM is dictated by Islam or not 7 and more work is needed to clarify this misperception. 3 Considering FGM is not a practice related to Islam, it is worth noting that religious leaders are often seen as 'guardians of the community' with the potential to reinforce campaign messages, an important aspect of creating successful campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst it is often older women in the family deciding on whether girls should undergo FGM, 3 men's views are also important as they too can either prevent or support the practice. 7 Consequently, three groups from the community were recruited -mothers, fathers and young women. The aim was to also interview young men, but none volunteered, potentially believing the topic was not relevant to them, or viewing it as an embarrassing topic to discuss.…”
Section: Participants and Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, uneducated women (Novak 2016). Similarly, men from specific sociodemographic backgrounds have been found to be more likely to favour FGM, for example, older and uneducated men (Fahmy et al 2010;Kaplan et al 2013;NPC and ICF International 2014;Varol et al 2015;Catania et al 2016). Additionally, men in professional occupations, for example doctors and nurses, would prefer FGM to end (Ibrahim et al 2013), presumably because they have knowledge of its health consequences.…”
Section: Factors Associated With Fgmmentioning
confidence: 99%
“…Studies have explored women's and children's knowledge and perceptions of the practice of FGM (Ahanonu and Victor 2014;Ajite et al 2016), and those of male adolescents in Nigeria (Adeniran et al 2015), however, only a few studies have explored the views of adult men about the tradition (Catania et al 2016). For example, Johnson-Agbakwu et al ( 2014) conducted a qualitative study among 40 Somali men and reported that all but one participant voiced their disagreement with FGM.…”
Section: Introductionmentioning
confidence: 99%